2021
DOI: 10.1093/pm/pnaa373
|View full text |Cite
|
Sign up to set email alerts
|

A Healing Journey with Chronic Pain: A Meta-Ethnography Synthesizing 195 Qualitative Studies

Abstract: Objective There is a large body of research exploring what it means for a person to live with chronic pain. However, existing research does not help us understand what it means to recover. We aimed to identify qualitative research that explored the experience of living with chronic pain published since 2012 and to understand the process of recovery. Design A synthesis of qualitative research using meta-ethnography. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 56 publications
2
41
0
Order By: Relevance
“…A recent study on health interventions for chronic pain suggested that interventions should focus on validating pain through meaningful and rational explanations and validating patients by listening to and valuing their stories. 35 In our study, therapists as well as patients mentioned the importance of these issues. However, the most important elements in providing symptom explanation according to therapists in our study is the body awareness exercise through which patients experience the body–mind interaction themselves.…”
Section: Discussionmentioning
confidence: 63%
“…A recent study on health interventions for chronic pain suggested that interventions should focus on validating pain through meaningful and rational explanations and validating patients by listening to and valuing their stories. 35 In our study, therapists as well as patients mentioned the importance of these issues. However, the most important elements in providing symptom explanation according to therapists in our study is the body awareness exercise through which patients experience the body–mind interaction themselves.…”
Section: Discussionmentioning
confidence: 63%
“…Almost every research article assumes measurement invariance in self-reported measures even though patients could change their internal standards of measurement (recalibration), the way they value different domains assessed by a multidimensional questionnaire (reprioritization) or modify of the construction of the latent variables (reconceptualisation) [55,56]. These modifications may bias our understanding of patients, their symptoms and their point of view, especially when making sense of pain (or reconceptualise pain) is an important step in patients' healing journey in chronic pain [57]. One should consider or test (even if it is a difficult task) the invariance hypothesis when assessing evolution of PROM or PREM in research, clinical and educational contexts.…”
Section: Build a Person-centred Care Osteopathymentioning
confidence: 99%
“…(38,(47)(48)(49) Incorporating positive narratives that reassure and educate the patient are consistent with current best practices. (50) When used correctly, language is a tool to enable and encourage; when used incorrectly, language may contribute to the maintenance of their pain state. (51) The massage therapist must be careful to avoid language that is overly pathoanatomical and suggests damage and poor prognosis, such as musculoskeletal components being "out of alignment" or "weak".…”
Section: Using Person-centred Communication and Shared Decision-makingmentioning
confidence: 99%